EFEITO DA FOSFINA SOBRE A â€œTRAÃ‡A DAS COLMEIASâ€, Galleria mellonella L. (PYRALIDIDAE, LEPIDOPTERA) (NOTA PRÃ‰VIA) - Nakano, Octavio; Amaral, Ã‰rico; Guerra, Milton de Souza (REVISTA DE AGRICULTURA, 2016)
EFEITO DA FOSFINA SOBRE A â€œTRAÃ‡A DAS COLMEIASâ€, Galleria mellonella L. (PYRALIDIDAE, LEPIDOPTERA) (NOTA PRÃ‰VIA)